2020
DOI: 10.1186/s12906-020-02982-9
|View full text |Cite
|
Sign up to set email alerts
|

Altitude impact on the chemical profile and biological activities of Satureja thymbra L. essential oil

Abstract: Background: Several agricultural or environmental factors affect plants' chemical and pharmacological properties.Methods: In this study, the essential oil of Libyan Satureja thymbra was isolated from plants collected during two successive years at two different altitudes; Wasita (WEO) and Safsaf (SEO), 156 and 661 m above sea level, respectively. Results: GC/MS allowed the identification of 21 and 23 compounds, respectively. Thymol prevailed in WEO (26.69%), while carvacrol prevailed in SEO (14.30%). Antimicro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 48 publications
1
33
0
Order By: Relevance
“…P. lhotzkyanum EO from this high altitude differed from samples collected from a low-altitude region 763 m in São Paulo -SP Brazil 8 , which showed bicyclogermacrene 21 and caryophyllene oxide 14 as major constituents. This difference in EO composition may be attributed to environmental such as more exposure to sunlight and genetic factors 9,10,44,45 . We also believe that an assessment of the impact of seasonality and circadian rhythm on EO of these species is necessary 11 .…”
Section: Discussionmentioning
confidence: 99%
“…P. lhotzkyanum EO from this high altitude differed from samples collected from a low-altitude region 763 m in São Paulo -SP Brazil 8 , which showed bicyclogermacrene 21 and caryophyllene oxide 14 as major constituents. This difference in EO composition may be attributed to environmental such as more exposure to sunlight and genetic factors 9,10,44,45 . We also believe that an assessment of the impact of seasonality and circadian rhythm on EO of these species is necessary 11 .…”
Section: Discussionmentioning
confidence: 99%
“…For that reason, it is doubtful to attribute the biological activity of essential oil to a particular constituent. Bioactivity could be due to the synergistic effects of all components [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The anthelmintic activity study was done using three different doses of each essential oil (1ml of 0.1%, 0.2%, and 0.3% v / v in 1% aqueous tween 80) against the earthworm Allolobophora caliginosa [ 1 , 21 ]. Briefly, an Anthelmintic test was applied on 24 worms.…”
Section: Methodsmentioning
confidence: 99%
“…[1,12] The plant growing sites' altitude is considered an important environmental factor that influences the composition and quantity of bioactive compounds in plants. [13] Moreover, some environmental abiotic and biotic factors, such as light, temperature, and radiation, are influenced by altitude. Cirak and Radusiene [14] reported that growing plant sites' altitude had stimulated secondary metabolism greatly as lower temperatures and higher UV-B radiation predominate at higher altitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the numerous studies on the altitude effects on plant content of bioactive constituents, [13,[16][17][18] to our knowledge, there is limited information on the altitudinal relationship of total phenols and flavonoids in honey. There has been less previous evidence for the direct effect of altitude on the honey content of polyphenols.…”
Section: Introductionmentioning
confidence: 99%